National trends in insulin resistance and β-cell dysfunction among adults with prediabetes: NHANES 2001–2016 - Hao-Jie Zhang (KeAi Communications Co., Ltd., 2021)
Background: Insulin resistance is the central abnormality and mechanism underlying the progression of cardiometabolic-based chronic diseases. This study aimed to evaluate the trends in insulin resistance and β-cell dysfunction from 2001 to 2016 among US adults with undiagnosed diabetes, prediabetes, and normal glucose regulation and to provide sex-specific information using data from National Health and Nutrition Examination Surveys (NHANES) 2001–2016. Methods: Data from 14,481 participants aged over 20 years from 8 consecutive 2-year cross–sectional cycles of the NHANES from 2001 to 2016 were used. Updated homoeostasis model assessment 2 (HOMA2: HOMA2%B for β-cell function and HOMA2IR for insulin resistance) was used as a surrogate measure. We defined the upper sex-specific tertile of HOMA2IR as insulin resistance and the lower corresponding tertile of HOMA2%B as low β-cell function. Results: In both sexes with undiagnosed diabetes, HOMA2%B (men, Ptrend = 0.118; women, Ptrend = 0.184) and HOMA2IR (men, Ptrend = 0.710; women, Ptrend = 0.855) remained stable over time. In the prediabetes group, both sexes exhibited significant increasing trends in HOMA2%B (men, Ptrend < 0.010; women, Ptrend < 0.010) and HOMA2IR (men, Ptrend < 0.010; women, Ptrend < 0.050). Adjusting for waist circumference mildly attenuated the trend in HOMA2IR and insulin resistance in men (Ptrend < 0.010), but it resulted in no significance in women (Ptrend = 0.196). In regard to normal glucose regulation, both sexes presented significant decreasing trends in low β-cell function (men, Ptrend < 0.050; women < 0.010) and attenuated trends in insulin resistance (men, Ptrend = 0.196; women, Ptrend = 0.121). Conclusions: Over 16 years, insulin resistance demonstrated an increasing trend in adult US population with prediabetes, while β-cell function showed a compensatory increasing trend. Identifying people with prediabetes early and focusing on reducing insulin resistance as the intervention core, especially controlling central obesity, might increase the opportunity for cardiovascular and diabetes risk reduction.